1998
DOI: 10.1007/bf03041997
|View full text |Cite
|
Sign up to set email alerts
|

Die Reliabilität radiologischer Befunde zur Differentialdiagnose der vertebralen Osteoporose

Abstract: Inter-rater reliability of more than 30 radiological findings was assessed in 4 German centres of the European Vertebral Osteoporosis Study (EVOS). One hundred randomly selected EVOS cases from the West-Berlin population, each contributing 2 lateral X-rays from the thoracic and lumbar spine respectively, were independently evaluated by 7 observers. All observers were medical doctors, 4 of them heads or members of clinical radiological departments. Thus each observer read 200 radiographs. Radiological alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In conclusioin, in prospective studies of vertebral deformity incidence in populations of women who are relatively unaffected by osteoporosis at the start of the study, MXA now seems to be the method of choice, given dosimetric considerations, the similar performance of morphometry using the two technologies and the uncertainties of qualitative assessment using conventional radiographs when expert radiographic assessors report the results in isolation from each another [4]. It may be wondered why a low radiation dose technology should peform so well in comparison with a higher-dose technology which achieves much better pictorial de®nition.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In conclusioin, in prospective studies of vertebral deformity incidence in populations of women who are relatively unaffected by osteoporosis at the start of the study, MXA now seems to be the method of choice, given dosimetric considerations, the similar performance of morphometry using the two technologies and the uncertainties of qualitative assessment using conventional radiographs when expert radiographic assessors report the results in isolation from each another [4]. It may be wondered why a low radiation dose technology should peform so well in comparison with a higher-dose technology which achieves much better pictorial de®nition.…”
Section: Discussionmentioning
confidence: 97%
“…Accurate identi®cation of prevalent and incident vertebral fractures is of central importance in epidemiologic studies and in the assessment of interventions for osteoporosis, but de®nition of vertebral fracture has proved problematic [4,5]. Qualitative assessment of vertebral deformities is inaccurate because of signi®cant inter-and intra-individual variations in vertebral dimensions, and in recent years a number of morphometric approaches have been devised in which individual vertebral heights in the lumbar and thoracic spine are compared with vertebra-speci®c data from a reference population [5±7].…”
Section: Introductionmentioning
confidence: 99%
“…In pilot work, we found a disturbing amount of disagreement between members of a panel of expert radiologists and clinicians who each evaluated a selection of normal and abnormal films to explore the possibility of decentralizing the reading of X-rays in the study. (30) This pilot clearly showed that clinical reading of X-rays without adequate safeguards to ensure the identity of criteria used to score osteoporotic vertebral fractures differs between centers. (30) There are other problems that, however, can make the achievement of accuracy and reproducibility in the reading of X-rays for incident fractures using vertebral morphometry difficult.…”
Section: Determinants Of the Size Of Incident Vertebral Deformitiesmentioning
confidence: 95%
“…(30) This pilot clearly showed that clinical reading of X-rays without adequate safeguards to ensure the identity of criteria used to score osteoporotic vertebral fractures differs between centers. (30) There are other problems that, however, can make the achievement of accuracy and reproducibility in the reading of X-rays for incident fractures using vertebral morphometry difficult. These include the variability in quality of X-rays taken in different centers, changes in personnel at the central morphometry center, and the increasing discrimination of the same personnel as they gain experience in point placement on film images between the first and second films.…”
Section: Determinants Of the Size Of Incident Vertebral Deformitiesmentioning
confidence: 95%
“…Part of the impetus for using vertebral morphometry rather than clinical assessment by an expert radiologist (as is usual in clinical practice) is the perception that experts do not always agree on what is a vertebral fracture [1], so that multicenter evaluations are unreliable or not reproducible in other centers. There are also some well-recognized limitations with vertebral morphometry.…”
Section: Introductionmentioning
confidence: 99%